Serum ANCA and Overall Mortality: A 10-Year Retrospective Cohort Study on 1,024 Italian Subjects - Brunetta, Enrico; Ramponi, Giacomo; Folci, Marco; De Santis, Maria; Morenghi, Emanuela; Vanni, Elena; Bredi, Elena; Furlan, Raffaello; Angelini, Claudio; Selmi, Carlo (Frontiers in Immunology, 2021)
BACKGROUND: Antineutrophil cytoplasmic antibodies (ANCA) are primarily involved in the pathogenesis of ANCA-associated vasculitides (AAV). However, ANCA may also be present in healthy subjects and in patients with autoimmune disorders different from AAV. We hypothesized that serum ANCA are associated with a worse prognosis in disorders other than AAV. OBJECTIVE: We investigated the association between the overall survival and the presence of serum ANCA in 1024 Italian subjects with various testing indications in a ten-year interval. METHODS: In this retrospective cohort study, a population of 6285 patients (many of whom were subsequently excluded due to our criteria) who tested for ANCA at a single center in ten years was considered and life status and comorbidities of subjects were collected. We compared the overall survival of ANCA-positive and ANCA-negative patients by means of Kaplan-Meier curves, while a multivariable adjusted Cox regression was used to evaluate the association between the ANCA status and the outcome (death) in terms of hazard ratios (HR) with 95% confidence intervals (CI). RESULTS: The positivity of pANCA increased significantly mortality (HR 1.60, 95% CI 1.10-2.32), while cANCA positivity failed to show a significant association (HR 1.43, 95% CI 0.77–2.68). The increased mortality rate was observed for both pANCA and cANCA in patients suffering from rheumatic disorders. No association was found between mortality and anti-MPO (HR 0.63, 95% CI 0.20-2.00) or anti-PR3 (HR 0.98, 95% CI 0.24-3.96) after adjusting for confounders. CONCLUSIONS: Serum pANCA and cANCA are independent negative prognostic factors in patients with concurrent autoimmune diseases.